Researching the conditions for renewing of fishing fleet by prospective types of large-tonnage vessels - Andrey I. Solomin (Известия ТИНРО, 2015)
Cost efficiency of projecting, shipbuilding and exploitation of new types of fishing vessels is analyzed for several existing fishery enterprises. Running costs per a catch day are calculated for certain vessels projects and leasing terms; the leasing procedure is described; the break-even points are evaluated. There is concluded that large enterprises or corporations with high volume of production are able to conduct profitable exploitation of large-tonnage vessels.